Caracterización fitoquímica del cedrón (Aloysia citrodora Paláu, Verbenáceas) en Argentina para su normalización - Di Leo Lira, Paola (2016)
Lemon verbena (Aloysia citrodora) is the most widespread native aromatic species in the world. The volatile fraction is one of its most prominent features. The main component of its essential oil (EO) is citral, which together with limonene are responsible for the characteristic aroma.\nFor its medicinal use, the nonvolatile fraction is also very important. Verbascoside has been identified as the major compound in this fraction and as the great responsible for its various bioactivities.\nThe development of this work allowed to know the phytochemical variability in wild and cultivated populations in Argentina and to establish quality standards for its different uses. The chemical composition of EO of 135 samples was determined by chromatography GC-FID-MS. By observing the differences in the qualitative and quantitative profiles they were grouped into six different chemotypes. Sabinone was isolated for the first time in an EO and identified by spectroscopic means.\nVerbascoside content was determined by HPLC in 52 samples. The average result was 2.1% P/P.\nThis information is expected to contribute to the drafting of quality standards for the Argentinian lemon verbena, allowing the choice of genetic material for cultivation using good agricultural management obtaining materials that comply with the market requirements.